LEVERAGING CORPORATE SOCIAL RESPONSIBILITY AS A TOOL TO ENHANCE STUDENT LEARNING EXPERIENCE - Aslinda Mohd Shahril; Mohd Shazali Md. Sharif (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Corporate Social Responsibility (CSR) is not only undertaken by corporate companies but is also commonly practiced by academic members of universities. As part of a teaching innovation practice, a CSR initiative through a Knowledge Transfer Program (KTP) was conducted, involving Master’s students and students from Kolej Vokasional (KV) Muar, Johor. The aim of this initiative was to address the limited exposure of KV students to culinary and hospitality education practices. Therefore, the objectives of this activity were to introduce KV Muar students to new knowledge and experiences through activities organized by UiTM students and lecturers. This initiative marks the first collaboration in academic activities between UiTM and KV Muar, Johor combining various activities such as career talks, table setting sessions, napkin folding, and mentor-mentee interactions. The contribution of this project to society is significant, as it provides KV Muar students with new knowledge and experiences. Through academic collaborations with UiTM, and activities like career talks and practical sessions, such as table setting and napkin folding, KV Muar students are equipped with practical skills that are valuable in both academic and professional settings.